Website using Silverlight and ASP.NET modules - Shastry, Arun P. (Kansas State University, 2009)
Developing websites that provide the user with a rich experience has become one of the most important needs of the present day world wide web. This website has been implemented using Microsoft Silverlight 2.0 - one of the front runners among technologies used for creating applications with a rich user experience and ASP.NET. The main objective of this project is to build parts of a website using Microsoft Silverlight – thus, showcasing the technology’s capabilities in improving user experiences on websites and also explore how these experiences are made possible from a programmer’s point of view. A part of the functionality of the website is also implemented as ASP.NET modules. The background code for both the parts is written in C#. NET.
Keywords: Silverlight; Website; Computer Science (0984)